Climate policies and labor markets in developing countries - Noe Reidt (ETH Zurich, CER-ETH - Center of Economic Research, 2021)
This paper investigates the impact of climate policies on the labor markets in developing countries characterized by a large informal economy. I conduct the analysis employing a dynamic general equilibrium model, which incorporates the three prevalent working groups in developing countries: informal self-employment, informal employment, and formal employment. To capture the mobility of workers between these groups, I use a search and match mechanism with search frictions for formal and informal firms and with on-thejob search. The model is calibrated to India to elaborate on the impact of climate policies envisioning a tax on energy with different redistribution schemes of the tax revenue. The results show that climate policies strengthening the position of the productive formal sector can lead to a triple dividend effect: emissions drop due to the energy tax, whereas the redistribution scheme increases the formal labor share and welfare. Developing countries with widespread informality can utilize climate policies to improve labor conditions while reaching their climate targets.
Keywords: C68; E26; J46; Q56; 330; development; climate policies; employment; search frictions; informality